2018
DOI: 10.1001/jama.2018.19329
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Variants Related to Gluteofemoral vs Abdominal Fat Distribution With Type 2 Diabetes, Coronary Disease, and Cardiovascular Risk Factors

Abstract: IMPORTANCE Body fat distribution, usually measured using waist-to-hip ratio (WHR), is an important contributor to cardiometabolic disease independent of body mass index (BMI). Whether mechanisms that increase WHR via lower gluteofemoral (hip) or via higher abdominal (waist) fat distribution affect cardiometabolic risk is unknown. OBJECTIVE To identify genetic variants associated with higher WHR specifically via lower gluteofemoral or higher abdominal fat distribution and estimate their association with cardiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
153
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(170 citation statements)
references
References 41 publications
15
153
2
Order By: Relevance
“…Obesity traits were causally related to higher risk of T2D, in keeping with previous studies (6)(7)(8)(9)(10)(11)19,64). We could not detect a sex difference in risk of T2D from higher WHR or WHRadjBMI.…”
Section: Diabetessupporting
confidence: 89%
See 3 more Smart Citations
“…Obesity traits were causally related to higher risk of T2D, in keeping with previous studies (6)(7)(8)(9)(10)(11)19,64). We could not detect a sex difference in risk of T2D from higher WHR or WHRadjBMI.…”
Section: Diabetessupporting
confidence: 89%
“…Even though some observational studies have suggested that WHR may be a stronger predictor of T2D risk in women than in men (18,19), studies investigating the effect on T2D risk from genetic predisposition to higher WHRadjBMI have not found evidence of sexual heterogeneity (6,9,11). In contrast, we found that BMI conferred a higher T2D risk in women than in men.…”
Section: Diabetescontrasting
confidence: 85%
See 2 more Smart Citations
“…Consistent with these findings, MIR196A1 miRNA levels are lower in endometrial tumors compared with healthy endometrial tissue [42]. There may also be a link between MIR196A1 and the endometrial cancer risk factors of obesity and insulinemia [43,44]: MIR196A1 miRNA is upregulated in gluteofemoral fat, which is associated with lower risk of diabetes [45]; and forced expression of the mouse homologue of MIR196A1 has been found to make mice resistant to obesity and prevent them from developing insulin resistance [46].…”
Section: Discussionmentioning
confidence: 64%